Simultaneous capture of NH3 and H2S using TiO2 and ZnO nanoparticles - laboratory evaluation and application in a livestock facility. Issue 1 (February 2020) - Valdes Labrada, Guadalupe Montserrat; Kumar, Suraj; Azar, Ruth; Predicala, Bernardo; Nemati, Mehdi
Graphical abstract: Highlights: TiO2 and ZnO both adsorbed NH3 and H2 S simultaneously but at different capacities. Increase of NH3 and H2S concentrations in the gas mixture led to higher adsorption capacities. NH3 adsorption was both physical and chemical but chemisorption was dominant at high temperatures. Sulfidation reaction involving ZnO and H2 S, favored by higher temperatures, was evident. Nano-based adsorption mitigated NH3 and H2 S emissions from a swine production facility. Abstract: Simultaneous removal of ammonia (NH3 ) and hydrogen sulphide (H2 S) from pre-mixed gases and stored swine manure gases were investigated in laboratory and semi-pilot scale systems and in a swine production facility, using TiO2 and ZnO nanoparticles. Increase of NH3 concentration in the mixture from 50 to 500 ppmv led to higher breakthrough and equilibrium adsorption capacities, while increase of temperature had an opposite effect. Equilibrium adsorption capacities at 22 °C were in the range 6.92–11.95 mg NH3  g −1 and 1.35–3.57 mg NH3  g −1 at 280 °C. Increase of H2 S concentration up to a certain level led to higher equilibrium adsorption capacities but no dependency between breakthrough adsorption capacity and H2 S concentration was observed. Both breakthrough and equilibrium adsorption capacities increased with the increase of temperature. The highest equilibrium adsorption capacity of 52.31 mg H2 S g −1 was obtained with 550 ppmv H2 S in the mixture at 140 °C, while the lowest value was 14.55 mg H2 S g −1 with 50 ppmv H2 S at 22 °C. At low temperature (22 °C) NH3 adsorption occurred through both physical adsorption and chemisorption, while at 280 °C chemisorption was the dominant mechanism. A sulfidation reaction involving ZnO and H2 S that was favored by higher temperatures was evident. Treating gases emitted from stored swine manure in a semi-pilot scale adsorption system led to complete elimination of NH3 and H2 S. Application of a nano-based air filtration-circulation system with ZnO and TiO2 nanoparticles in a swine production room during manure handling led to removal efficiencies of 67–100% for H2 S and 50–100% for NH3 .